A Self-View on Teacher Leadership among Early Childhood Education English Teachers through Their Reading Classes - Anita Wijayanti; Dyah Setyowati Ciptaningrum; Jamilah Setyowati Ciptaningrum (Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigates the natures of teacher leadership in early childhood education, specifically focusing on English reading class. Through questionnaires, the research explores the connections among teacher leadership perspectives, practices, and identity. The findings verify the significance of teacher leadership perspectives in shaping educators' beliefs about their role in improving student learning performance. Teachers possessing a strong sense of leadership are more likely to create literacy-rich environments, engage in collaborative practices, and support their students' needs. In addition, effective teacher leadership practices, such as involving parents in supporting children's reading development and utilizing innovative instructional strategies, play a crucial role in enhancing student outcomes. The results also reveal the relationship between teacher leadership perspectives, practices, and identity indicating that positive perspectives and effective practices contribute to the development of a strong teacher leadership identity. Nurturing both perspectives and practices allows educators to develop a sense of agency and empowerment. By prioritizing the development of teacher leadership, educational institutions can create more supportive and innovative learning environments. Professional development programs should be designed to equip teachers with the knowledge, skills, and dispositions necessary to assume leadership roles. Additionally, school leaders should foster a culture that values and supports teacher leadership. In conclusion, this study offers valuable insights into the complexities of teacher leadership in early childhood English education. By understanding the connectedness between perspectives, practices, and identity, educators can enhance their leadership capacity and ultimately improve student learning outcomes.